Pengaruh Clay Therapy terhadap Kecemasan Anak Usia Prasekolah yang Menjalani Prosedur Invasif di RSUD Al-Ihsan - Depi Lukitasari (Sehat MasadaJurnal, 2019)
Background. During hospitalization large number of invasive procedure recived by patient and preceived as threatening and anxiety experience. One of the invasive procedures that commonly done is the venous blood extraction. The children in preschool age preceived venous blood extraction as something that endanger the integrity of the body and lead to anxiety experience. To reduce the anxiety during the venous blood extraction, a nurse could perform a clay theraphy. The aim of this research is to ascertain the effect of clay therapy toward scoreof anxiety in preschool age children that undergoing venous blood extraction in RSUD Al-Ihsan.Methode. The study was quasi-experiment with nonequivalent control group posttest only. A total of 34 children who recieve venous blood extraction was assigned into 2 group, 17 children in control and 17 children in intevention. The children anxiety level measured using anxiety observation sheet before the procedure complete. Data were analyzed used independent t test for bivariate and logistik regresion for multivariate. Result Findings. The results show a significat difference in anxiety score between control group and intervention group with p-value 0,001 < α 0.05 which means there is impact of clay therapy to level anxiety in preschool age children undergoing invasive procedure in RSUD Al-Ihsan. Conclusion. This research indicate that clay therapy may be used to reduce anxiety in children that undergoing venous blood extraction.